Complete biosynthesis of salicylic acid from phenylalanine in plants - Bao Zhu; Yanjun Zhang; Rong Gao; Zhihua Wu; Wei Zhang; Chao Zhang; Penghong Zhang; Can Ye; Linbo Yao; Ying Jin; Hui Mao; Peiyao Tou; et al. (Nature, 2025)
Abstract Salicylic acid (SA) is a pivotal phytohormone for plant responses to biotic and abiotic stresses. Plants have evolved two pathways to produce SA: the isochorismate synthase and phenylalanine ammonia lyase (PAL) pathways1. Whereas the isochorismate synthase pathway has been fully identified2–4, the PAL pathway remains incomplete. Here we report the full characterization of the PAL pathway for SA biosynthesis via functional analysis of rice (Oryza sativa) SA-DEFICIENT GENE 1 (OSD1) to OSD4. The cinnamoyl-coenzyme A (CoA) ligase OSD1 catalyses the conversion of trans-cinnamic acid to cinnamoyl-CoA, which is subsequently transformed to benzoyl-CoA via the β-oxidative pathway in peroxisomes. The resulting benzoyl-CoA is further converted to benzyl benzoate by the peroxisomal benzoyltransferase OSD2. Benzyl benzoate is subsequently hydroxylated to benzyl salicylate by the endoplasmic reticulum membrane-resident cytochrome P450 OSD3, which is ultimately hydrolysed to salicylic acid by the cytoplasmic carboxylesterase OSD4. Evolutionary analyses reveal that the PAL pathway was first assembled before the divergence of gymnosperms and has been conserved in most seed plants. Activation of the PAL pathway in rice significantly enhances salicylic acid levels and plant immunity. Completion of the PAL pathway provides critical insights into the primary salicylic acid biosynthetic pathway across plant species and offers a precise target for modulating crop immunity.